Persepsi Guru SMA di Kota Sungai Penuh Tentang Pembelajaran Dalam Jaringan - Tiara Tiara; Suci Mahabbati; Indah Kencanawati; Lia Angela (Universitas Indraprasta PGRI Jakarta, 2023)
Online learning is an alternative learning system, especially when face-to-face learning cannot be held. This study aims to analyse the perceptions of high school teachers in the city of Sungaipuh about the online learning system and find out the problems of teachers in implementing it. This research is quantitative research with a descriptive approach. The population of this study were high school teachers and equivalent schools in Sungaipuh with a sample of 182 people. Data was collected through surveys using open and closed questionnaires. The questionnaires were distributed in December 2021 via Google Form. Data were analysed descriptively by presenting tables. The results of the study showed that the implementation of online learning in high schools in Sungaipuh City is still considered ineffective due to several problems faced, including the readiness of educators in organizing learning as well as the quality and quantity of supporting facilities. Limited digital resources, such as internet networks, are the most dominant difficulties faced by teachers in carrying out online learning.